Application of Stainless Steel Laser Welding Process Specification in Rail Vehicles - Ansong LYU; Jinhua SU; Zeyun YANG; Dongguang PIAO; Wenxia LI; Xiaohui HAN (机车电传动)
The development history of laser welding technology in the rail transit manufacturing process of stainless steel vehicle body was introduced, and the main technical background, standard content and formulation principles of the national standard GB/T 37778—2019 "Recommended process specification for laser welding of stainless steel" were interpreted in emphasis, which provided reference for the promotion and application of laser welding technology in the rail transit industry, and further would promote the application of laser welding technology in the stainless steel products.